The Exterior and Driver Cabs of Locomotive CC300 Based on Integrated Digital Design - Agus Windharto (Institut Teknologi Sepuluh Nopember, 2014)
The research backgrounds are regarding amount growth of rail passenger that caused by impacts of Indonesian Economic development. The demand of new Locomotive and wagon Railways is increasing, this condition not followed by the growth of domestic industry ability in design, production and manufacturing. At this time being, this national demand full filled by imported products and licensing collaboration between PT KAI - PT INKA with General Electric. On the initiative of PT KAI and PT INKA, the programmed design prototype for locomotive cc300 double cabin conducted . In this synergetic program, Engineering design studies and technology transfer carried out by PT INKA team, while exterior -drivers cabs design - human factor study carried out by ITS team.The research proposition are not well defined yet of design reference design for the exterior and driver cabs . Demand for integrated design and manufacturing process need to be answered. Lack of national stakeholder trust in national railway industry train designing and manufacturing locomotives independently.The research purpose is to provide design reference for CC300 locomotive exterior and the cab driver. Integrating design engineering process to produce products that meet the better standards for locomotive in form of QCD ( Quality , Cost and Delivery ) . Convincing National stakeholder in the National Railways to invest on design and production of locomotives in Indonesia.The research method is IDD ( Integrated Digital Design ) that flow of research phase from the study concept interior exterior shape , stage geometry , ergonomics studies , and model studies to prototyping stages.This research result is CC300 Locomotive Exterior design, Driver Cabs design, scaled model and prototype that recently on static and dynamic test.